Gross Inflows Gone Wild : Gross Capital Inflows, Credit Booms and Crises - Calderon, Cesar; Kubota, Megumi (2013)
The main goal of the paper is to examine whether surges in private capital inflows lead to credit booms. The authors built a quarterly database on gross capital inflows, credit to the private sector, and other macro-financial indicators for a sample of 71 countries from 1975q1 to 2010q4. Identifying credit booms is not trivial: they use different criteria implemented in the literature. The estimates suggest that: (i) Surges in gross private capital inflows are overall good predictors of credit booms. (ii) The likelihood of credit booms is higher if the surges in foreign flows are driven by private other investment inflows and, to a lesser extent, portfolio investment inflows. (iii) Surges in gross inflows are also good predictors of credit booms that end up in a financial crisis -- "bad" credit booms. This finding holds even after controlling for the appreciation of the local currency and the build-up of leverage. (iv) Bad credit booms are more likely to occur when surges are driven by other investment inflows. At best, foreign direct investment inflow-driven surges help mitigate the incidence of this type of credit boom. (v) The predictive ability of gross other investment inflows is primarily driven by bank inflows. (vi) Consistent with the literature, the analysis finds that the build-up of leverage and the real overvaluation of the currency help predict credit booms that are followed by a systemic crisis. Controlling for these factors, capital flows are still a significant predictor of credit booms.